Modelo ideal de tributação na cadeia de produtiva do hidrogênio verde no Estado do Ceará: royalties como alternativa - Araújo, Fábio Hipólito de (2024)
Green hydrogen has been presented as an energy vector and a clean and renewable energy source capable of facing the challenges of this sector, becoming a viable alternative to fossil fuels. This paper aims to present the development of green hydrogen in Brazil, seeking to analyze the regulatory and taxation approach of this energy matrix widely viewed as a factor for the development of the State of Ceará. The paper will seek to identify and discuss the initiatives in Brazil for the development of energy through green hydrogen, from the perspective of a “green economy”, low-carbon production and sustainable development, but the need for financing of the public sector through taxation and/or royalties has been taken into account. It is worth noting that the tax charged on electricity supply operations, mainly the ICMS, a state tax, is a vital source of revenue collection for the federated states, which, however, will not generate revenue for the State of Ceará if H2v, a product derived from electricity, is destined for export.